DISTILLED BEVERAGE FROM FERMENTED GRAPES (REMUNOM, 2026)
This study evaluates the behavior of a distillation column with 10 perforated plates in obtaining wine distillate. The fermented liquid with 12 GL was obtained from a mixture of ethyl alcohol and water and fed into a column with 10 perforated plates operating at a reflux ratio of 4.. A study of the differential distillation performance was carried out. Therefore, the objective of this study was to evaluate the performance of a perforated plate distillation column in a pilot plant located at the Instituto Superior de Engenharia do Porto, in Portugal. The results showed that the distillate concentration, compared to differential distillation, is approximately three times higher when the same quantity of distillate is obtained; the intermediate data are valuable for supporting studies on wine distillation for obtaining distilled beverages